1983
DOI: 10.1093/infdis/148.3.436
|View full text |Cite
|
Sign up to set email alerts
|

Relative Titers of Antibodies to Individual Polypeptide Antigens of Herpes Simplex Virus Type 1 in Human Sera

Abstract: Human immune sera were analyzed by an immunoblot procedure in order to identify which polypeptides of herpes simplex virus type 1 were recognized and to determine the relative concentrations of antibodies to individual viral antigens. The strongest reactivity in all immune sera examined was directed against the three major herpes simplex virus-specific glycoprotein antigens (gAB, gC, and gD) and a series of uncharacterized low-molecular-weight polypeptides. Titers of antibody to the gC and gD antigens varied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 35 publications
8
54
0
Order By: Relevance
“…The observation that plasma without an identifiable reaction to gD by immunoblotting was reactive in an ELISA using cloned gD as the antigen (our unpublished results) also suggests that immunoblotting may not be as sensitive as other methods for detection of antibody to this protein. Norrild et al (1981) also noted that the major reactive polypeptides were not the HSV-1 glycoproteins, although Eberle & Mou (1983) have reported strong responses to gB and gD in patients with recurrent HSV-1 infections in a system similar to ours. Preliminary studies in our laboratory have also suggested that weanling guinea-pigs, such as those used in this study, do not respond as well to gB and gD as do adult guinea-pigs (unpublished data).…”
Section: Discussionsupporting
confidence: 74%
“…The observation that plasma without an identifiable reaction to gD by immunoblotting was reactive in an ELISA using cloned gD as the antigen (our unpublished results) also suggests that immunoblotting may not be as sensitive as other methods for detection of antibody to this protein. Norrild et al (1981) also noted that the major reactive polypeptides were not the HSV-1 glycoproteins, although Eberle & Mou (1983) have reported strong responses to gB and gD in patients with recurrent HSV-1 infections in a system similar to ours. Preliminary studies in our laboratory have also suggested that weanling guinea-pigs, such as those used in this study, do not respond as well to gB and gD as do adult guinea-pigs (unpublished data).…”
Section: Discussionsupporting
confidence: 74%
“…High titres of antibody to gD and gB are also seen in quantitative immunoelectrop horetic studies on human sera (Vestergaard, 1979). There is generally good agreement between our results and those of Eberle and Mou (1983) except for the 75 x 103-m01. wt protein which was not a major protein in their studies.…”
Section: Discussionsupporting
confidence: 87%
“…(lo3) 44 and 42 were not precipitated in these studies, or were only minor proteins in immunoprecipitates. This disparity has previously been recognised by Eberle and Mou (1983). These proteins are probably related to the p40 protein purified from HSV nucleocapsids by Heilman et al (198 1) because monoclonal antisera to p40 (Zweig et al, 1980) bind to a series of proteins ranging in mol.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations